Fostering Critical Thinking Skills Through Argumentative Writing - Susana Widyastuti (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract: The urgency for developing students’ critical thinking (CT) abilities has left English as a Foreign Language (EFL) teachers trying hard to integrate CT into their teaching practices. This study highlights the role of language as a way of thinking, judging and assessing. It seeks to investigate how the elements of CT are displayed in students’ essay so as to reveal the development of their CT skills. The data are in the form of essay written by the fourth semester Indonesian students taking essay writing course. The analysis is based on Stapleton’s criteria of CT (2001), i.e. claims, kinds of reasoning, the extent of evidence, recognition of opposing arguments and refutation, and fallacies. The results show that there are many weak arguments in the essays due to the insufficiency of reasons and evidence. It is highly possible for an essay to have multiple arguments. However, the logical correlations between them are not clearly articulated in the essays and many students fail to show them. Students also lack of refutation skills as they tend to accept a claim from other sources without trying to judge and evaluate it. While most conclusions are in the form of suggestion, they can be made better by clearly showing the position of the writer in relation the arguments posed in the essay. Fallacies are mostly found in the form of generalization and over-simplification. The results are expected to give insights to teachers about how CT skills could be effectively taught and improved in writing classes.Keywords: argumentative writing, critical thinking (CT), English as a Foreign Language (EFL)Mengembangkan Kemampuan Berpikir Kritis Melalui Menulis Argumentatif Abstrak: Pentingnya mengembangkan kemampuan berpikir kritis (critical thinking atau CT) mahasiswa telah membuat para pengajar English as a Foreign Language (EFL) berusaha keras mengintegrasikan kemampuan berpikir kritis dalam pengajaran mereka. Penelitian ini menggarisbawahi peran bahasa sebagai sarana berpikir, menilai, dan mengevaluasi. Penelitian bertujuan untuk menggali bagaimana elemen-elemen berpikir kritis ditunjukkan dalam teks dan mengkaji perkembangan berpikir kritis dalam teks. Data berbentuk teks essay yang ditulis oleh mahasiswa semester 4 yang mengambil matakuliah Essay Writing. Data dianalisis berdasarkan kriteria Critical Thinking (CT) oleh Stapleton (2001), yaitu argument, reason, evidence, opposition and refutation, conclusion, dan fallacy. Hasil penelitian menunjukkan bahwa argumen sering lemah karena tidak didukung oleh alasan dan bukti yang cukup. Suatu esai sangatlah mungkin mengandung banyak argumen. Namun demikian, hubungan logis antar argumen tersebut tidak jelas dalam esai dan bahkan banyak mahasiswa gagal menunjukkan hubungan tersebut. Mahasiswa juga lemah dalam hal refutation skill karena mereka cenderung menerima klaim dari sumber lain begitu saja tanpa mencoba mengevaluasi dan mempertanyakannya. Kebanyakan kesimpulan berbentuk saran dan bisa dibuat lebih baik dengan menyatakan dengan jelas posisi penulis dalam menanggapi argumen-argumen yang dikemukakan di awal. Fallacy kebanyakan dalam bentuk generalisasi dan penyederhanaan berlebihan. Hasil penelitian ini diharapkan dapat memberikan masukan tentang bagaimana kelas menulis dapat dirancang secara efektif supaya dapat menumbuhkan baik kemampuan berpikir kritis maupun kemampuan berbahasa.Kata kunci: tulisan argumentatif, berpikir kritis, English as Foreign Language (EFL)